2003
DOI: 10.1073/pnas.232715799
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structure of hemoglobin in solution

Abstract: Many important proteins perform their physiological functions under allosteric control, whereby the binding of a ligand at a specific site influences the binding affinity at a different site. Allosteric regulation usually involves a switch in protein conformation upon ligand binding. The energies of the corresponding structures are comparable, and, therefore, the possibility that a structure determined by x-ray diffraction in the crystalline state is influenced by its intermolecular contacts, and thus differs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
210
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(230 citation statements)
references
References 28 publications
19
210
0
1
Order By: Relevance
“…Along the new pathway, it is still valid (9,14) to consider hemoglobin as a dimer of αβ-dimers in which the C2 symmetry between the two αβ-dimers is essentially maintained. This behavior is consistent with a recent NMR study showing that carbon monoxyhemoglobin, while undergoing its quaternary transition between the R and R2 states (R2 is a low-salt form), retains C 2 symmetry in solution (29). It also is consistent with the Monod-WymanChangeux model of cooperativity (12), in which the protein retains its symmetry at the quaternary level.…”
Section: Discussionsupporting
confidence: 91%
“…Along the new pathway, it is still valid (9,14) to consider hemoglobin as a dimer of αβ-dimers in which the C2 symmetry between the two αβ-dimers is essentially maintained. This behavior is consistent with a recent NMR study showing that carbon monoxyhemoglobin, while undergoing its quaternary transition between the R and R2 states (R2 is a low-salt form), retains C 2 symmetry in solution (29). It also is consistent with the Monod-WymanChangeux model of cooperativity (12), in which the protein retains its symmetry at the quaternary level.…”
Section: Discussionsupporting
confidence: 91%
“…We have already reported that the solution structure of HbCO A is a dynamic ensemble of the R and R2 crystal structures (23). While additional research is needed to gain a deeper insight, there is sufficient information to suggest that a dynamic ensemble may exist in the deoxy form as well.In conclusion, the plasticity and dynamic picture of hemoglobin is consistent with the emerging view of allostery as a change in population distribution of an ensemble of structures, rather than the equilibrium of only two discrete conformations, upon binding of ligand (6,8,23,(42)(43)(44)(45). Hence, in order to understand how hemoglobin functions as an efficient oxygen carrier in our physiological system, we need to know the structure, dynamics, and function of this protein in solution.…”
supporting
confidence: 69%
“…Fitting was done using singular value decomposition (SVD) (37) or non-linear least-squares methods. Analysis included a comparison of experimental RDCs with back-calculated RDC values as described previously (23). Both root-mean square deviation (RMSD) and chi square (χ 2 ) values have been used to characterize the quality of the fit between the experimental and back-calculated RDCs.…”
Section: Rdc Analysismentioning
confidence: 99%
“…The calculated number of adsorbed water molecules upon haemoglobin's oxygen uptake varies from Ϫ65 to ϩ20 (Table 2) smaller than ϩ65 Ϯ 4 (4) inferred from OSA. It is emphasised that the multiple results of ⌬NЈ 21 obtained from my theory is due to the uncertainty regarding the structures of deoxygenated and oxygenated states (37,38). The expulsion of camphor from cytochrome P450cam, according to Eq.…”
Section: Osmotic Stress Analysis May Overestimate the Number Of Watermentioning
confidence: 96%
“…They are summarised in Table 1. For hemoglobin, the conformations for deoxygenated and oxygenated structures are still under debate (37,38). Therefore, I have followed LiCata and Allewell (17) and calculated ⌬V E s under all possible conformational changes between the deoxygenated and oxygenated structures determined thus far (see Table 1).…”
Section: Osmotic Stress Analysis May Overestimate the Number Of Watermentioning
confidence: 99%